Effect of Two Seaweed Products on Radish (Raphanus sativus) Growth Under Greenhouse Conditions - Ramal Yusuf; Paul Kristiansen; Nigel Warwick (Universitas Tadulako, 2015)
Several studies have revealed a wide range of beneficial effects of seaweed products applications on plants growth and development. Seaweeds may cause different effect in plant responses because there are a range possible factors acting in concert. These factors may include to the amount of plant growth regulator (PGR) and nutrients present in the products. PGR activity in two seaweed products (Maxicrop® and Seasol®) was investigated using Radish (Raphanus sativus). Treatments included a control, standard concentrations of the seaweed Products (SS1 and MC1), 2 and 4 times the recommended rates (SS2, SS4, MC2 and MC4) ashed seaweed products (SS-ash and MC-ash), and equivalent amounts of N, P and K to that found in seaweed products (SS-NPK and MC-NPK). The results obtained show that both Maxicrop® and Seasol® can significantly increase crop performance. Maxicrop® increased chlorophyll content and root and shoot growth, while Seasol® only increased the chlorophyll content.